Production of carotenoids by Rhodotorula mucilaginosa using glucose and cassava wastewater and a comparison between ethanol, methanol and DMSO in their extraction - Dardani, Carolina Sangalli [UNESP]; Machado, Whallans Raphael Couto [UNESP]; Duarte, Ana Lúcia Ferrarezi; Oliveira, Giovana da Costa [UNESP]; Castilhos, Maurício Bonatto Machado de; Del Bianchi, Vanildo Luiz [UNESP] (Elsevier, 2024)
Reports of metabolic alterations resulting from synthetic pigments has stimulated research into natural ones. Carotenoids production using microorganisms has been stimulated due to the fact that they are considered naturals and have a high production rate. The cost can be reduced when agro-industrial coproducts are used as substrate. Additionally, this process requires an efficient pigments extraction, traditionally using dimethylsulfoxide (DMSO). This study aimed to formulate a culture medium composed by glucose and cassava wastewater for the action of Rhodotorula mucilaginosa URM 7409 that enables efficient production of volumetric carotenoids and the investigation of different extraction methods. The tests used glucose concentrations between 25.86 and 54.14 g/L and cassava wastewater between 3.17 and 8.83% v/v, while the extraction was carried out using a combination of ultrasound or glass beads with DMSO, methanol or ethanol. The results showed an increase of 92.89% in the efficiency of volumetric carotenoid production when the culture medium was composed by 8% v/v of cassava wastewater and 50 g/L of glucose compared to a medium that contained 4% v/v of the coproduct and 30 g/L of glucose. Also, regardless of the combined technique, there was no significant difference between DMSO and ethanol in the compounds extraction. The use of methanol combined with these techniques, in contrast, resulted in less efficient extractions. The study shows the potential of cassava wastewater and glucose for microbial carotenoids production and the ethanol efficiency in the extraction of these compounds, with ethanol producing less toxic extracts for use in the different industries.
Keywords: Agro-industrial coproducts; Alternative solvents; Extraction; Pigments; Yeasts